2013
DOI: 10.1007/s10549-013-2730-8
|View full text |Cite
|
Sign up to set email alerts
|

Favorable modulation of benign breast tissue and serum risk biomarkers is associated with >10 % weight loss in postmenopausal women

Abstract: We conducted a phase II feasibility study of a 6 month behavioral weight loss intervention in postmenopausal overweight and obese women at increased risk for breast cancer and the effects of weight loss on anthropomorphic, blood, and benign breast tissue biomarkers. 67 women were screened by random peri-areolar fine needle aspiration (RPFNA), 27 were registered and 24 participated in the interventional phase. The 24 biomarker evaluable women had a median baseline BMI of 34.2 kg/m2 and lost a median of 11% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 74 publications
8
63
0
1
Order By: Relevance
“…Our results on hsCRP are in line with several previous diet or exercise weight loss studies in healthy postmenopausal women (14,27,(30)(31)(32)(33)(34). Results of exercise-only interventions in a comparable population are mixed.…”
Section: Discussionsupporting
confidence: 88%
“…Our results on hsCRP are in line with several previous diet or exercise weight loss studies in healthy postmenopausal women (14,27,(30)(31)(32)(33)(34). Results of exercise-only interventions in a comparable population are mixed.…”
Section: Discussionsupporting
confidence: 88%
“…For premenopausal women who were not regularly menstruating, follicular phase of cycle was confirmed by FSH, estradiol, and progesterone levels. For the RPFNA procedure, two sites per breast were aspirated under local anesthesia as previously described with needle tip preferentially guided to areas of increased resistance [24, 30]. One-fifth of the RPFNA material was immediately placed in 0.25 ml aliquots of phosphate buffered saline in cryovials, placed in liquid nitrogen and transferred to a −80° C freezer within 12 h until assessments for fatty acid analyses, adipocytokines (Luminex®), gene expression (RT-qPCR), and proteomics.…”
Section: Methodsmentioning
confidence: 99%
“…Fasting blood [30] was obtained at the on-study visit and at 6 months within 24 hours of scheduled drug discontinuation. Insulin, glucose, adipocytokines and fatty acid analyses were performed on fasting blood.…”
Section: Methodsmentioning
confidence: 99%
“…This is consistent with findings that calorie restriction protects mice from colonic neoplasia and reduces COX2 expression (171). Weight loss in obese, postmenopausal women has been reported to improve serum biomarkers of breast cancer risk, including SHBG, bioavailable estradiol, insulin, C-reactive protein, adiponectin, and leptin (172). Similarly, a large mixed-weight population study found that all-cause weight loss was associated with reduced colon cancer risk (173).…”
Section: Effects Of Weight Loss On Inflammation and Cancer Riskmentioning
confidence: 97%